Answers

The Brainliest Answer!
2014-08-31T00:43:50+05:30
For first stone 
h = 49m
g = 9.8m/s²
t = ?
u = 0
apply 
h = ut + gt²/2
49 = 0 + 9.8t²/2
t² = 10
t = √10 = 3.16s
for second stone
t = 3.16 - 1 = 2.16s
h = 49m
g = 9.8m/s²
u = ?
again apply
h = ut + gt²/2
49  = u*2.16 + 9.8*2.16²/2
49 = 2.16*u + 22.86
26.14/2.16 = u
u = 12.10m/s

 
3 3 3
Thnx but again ambiguity striked my mind.........why is u not equal to 0 for the second stone?
2014-08-31T22:53:54+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let\ us\ take\ g\ =\ 9.8\ \frac{m}{sec}. \\ \\ 1st stone: \\ \\ \\ s = ut + \frac{1}{2} g t^2 \\ \\ 49 = 0\ t + 1/2 * 9.8 t^2 \\ \\ t = √10\ sec = 3.162\ sec \\ \\ The\ second\ stone\ traveled\ for\ 3.162\ -\ 1 \ seconds\ =\ 2.162\ sec. \\ \\ \\ 2nd stone: \\ \\ s = u t + \frac{1}{2} g t^2 \\ \\ 49 = u\ 2.162 + \frac{1}{2} * 9.8 * 2.162^2 \\ \\ Simplify, \ \ \ u\ =\ 12.07\ m /sec \\


0